The Role of Organizational Behavior Dimensions in Achieving Organizational Sustainability: The Moderating Impact of Human Resource Development in the Iraqi Construction Sector - Ali Saadi , Ibraheem (Journal of Economics and Administrative Sciences, 2025)
This empirical research aims to examine the relationship between three core dimensions of Organizational Behavior (OB), namely, Organizational Commitment (ORC), Organizational Structure (OST), Employee Engagement (EME), and Organizational Sustainability (OS) within medium and large-scale construction firms operating in Iraq. In addition, the study explores the moderating role of Human Resource Development (HRD) on the interactions between these OB elements and OS. A structured questionnaire was administered to 216 senior executives, including CEOs and senior managers, yielding 161 valid responses that were analyzed using SPSS. The findings confirm that ORC, OST, and EME are all significantly associated with OS. However, HRD only demonstrated a moderating effect on the relationship between OST and OS, while its influence on the connections involving ORC and EME was not statistically significant. These results contribute to the OB and sustainability literature by clarifying how specific behavioral factors influence sustainability outcomes in the construction industry. The study also offers practical guidance for organizational leaders on the strategic use of HRD to reinforce OB, particularly in the context of formal organizational structures, enhancing their responsiveness to sustainability challenges.